TANTANGAN PEMBELAJARAN DARING PADA PENDIDIKAN ANAK USIA DINI - Trisnadewi Komang (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
This study aims to determine how teachers in early childhood education units face the challenges of online learning during this pandemic. This study focuses on challenges in each learning component which includes teachers, students, curriculum, context, methods and tools. The method in this study includes data collection, analysis and data presentation. This Study used a questionnaire as a method to obtain primary data from teachers in early childhood education units who use online learning. After the data is obtained, then the data is analyzed. The results of the questionnaire are read as a whole and then grouped, given an explanation and a conclusion is drawn. There was a total of 20 teachers as respondents in this study. The results obtained that all components of learning have their own challenges so that teachers need to make more preparations than before when learning in class. Things that are taken into consideration in an effort to overcome the challenges faced are not only in terms of the ability of the teacher itself, but also the abilities of students and parents.